The Analysis of Survival Strategies in Small Medium Enterprises During Coronavirus Pandemic - Sudarmiatin Sudarmiatin (Profesional Muda Cendekia Publishing, 2022)
This study aims to (a) describe the problems faced by SMEs during the Pandemic and the capacity of SMEs in solving these problems (b) analyze the survival strategy of SMEs in order to survive during the pandemic. This type of research is a qualitative case study. The research location is in Malang Raya, which includes the city of Malang, Malang district and the city of Batu, East Java. The research subjects were 30 business managers of fashion SMEs in Malang, consisting of 10 owners and 20 employees. Collecting research data through interviews, observation and documentation. Data analysis uses SWOT analysis which includes strengths, weaknesses, opportunities and threats. The results showed that the problem faced by fashion MSME actors during the Covid 19 pandemic in Greater Malang was the decline in the number of sales until some went out of business. Most of the fashion MSME managers have not been able to operate digital marketing, so they still hope that consumers will come to buy directly to the store. Survival strategies are recommended for MSMEs to survive during the pandemic: a) Adaptation to changes in people's behavior during the pandemic. (b) Increasing mastery of technology both through training and self-study (c) Expanding target consumers from offline market to offline and online. (d) Adding online marketing networks through resellers in the marketplace, (e) Diversifying products, both main and additional products according to community needs during the pandemic